Maternal treatment with short-chain fatty acids modulates the intestinal microbiota and immunity and ameliorates type 1 diabetes in the offspring. - James C Needell; Diana Ir; Charles E Robertson; Miranda E Kroehl; Daniel N Frank; Danny Zipris (PLoS ONE)
We recently hypothesized that the intestinal microbiota and the innate immune system play key roles in the mechanism of Kilham Rat Virus-induced type 1 diabetes in the LEW1.WR1 rat. We used this animal model to test the hypothesis that maternal therapy with short-chain fatty acids can modulate the intestinal microbiota and reverse virus-induced proinflammatory responses and type 1 diabetes in rat offspring. We observed that administration of short-chain fatty acids to rat breeders via drinking water prior to pregnancy and further treatment of the offspring with short-chain fatty acids after weaning led to disease amelioration. In contrast, rats that were administered short-chain fatty acids beginning at weaning were not protected from type 1 diabetes. Short-chain fatty acid therapy exerted a profound effect on the intestinal microbiome in the offspring reflected by a reduction and an increase in the abundances of Firmicutes and Bacteroidetes taxa, respectively, on day 5 post-infection, and reversed virus-induced alterations in certain bacterial taxa. Principal component analysis and permutation multivariate analysis of variance tests further revealed that short-chain fatty acids induce a distinct intestinal microbiota compared with uninfected animals or rats that receive the virus only. Short-chain fatty acids downregulated Kilham Rat Virus-induced proinflammatory responses in the intestine. Finally, short-chain fatty acids altered the B and T cell compartments in Peyer's patches. These data demonstrate that short-chain fatty acids can reshape the intestinal microbiota and prevent virus-induced islet autoimmunity and may therefore represent a useful therapeutic strategy for disease prevention.